A subchronic application period of glucocorticoids leads to rat cognitive dysfunction whereas physostigmine induces a mild neuroprotection - Wüppen, Katrin; Oesterle, Dirk; Lewicka, Sabina; Kopitz, Jürgen; Plaschke, Konstanze (Journal of neural transmission, 2010)
The cholinergic neurotransmitter system and prolonged glucocorticoid-induced stress can affect cognitive functions in opposite ways. While pharmacological enhancement of cholinergic neurotransmission is known to induce neuroprotective effects, chronic glucocorticoids impair cognitive functions. Up to now, there is no consensus as to whether a subchronic stress period of several days would affect cognitive function. The goal of this study was to investigate whether or not repeated applications of physostigmine over 3 days lead to protective effects on rat spatial cognitive abilities in contrast to the deteriorating effect on rat cognitive function after corticosterone treatment. Furthermore, we wanted to investigate in what extent this cognition-modulating effect is associated with rat cerebral acetylcholinergic system. Male adult rats (n = 40) were randomly divided into four groups with n = 10 per group: (I) placebo-, (II) corticosterone- (15 mg/day), (III) physostigmine- (0.014 mg/day), and (IV) physostigmine + corticosterone-treated rats. Body mass and plasma corticosterone concentrations were measured. Psychometric investigations were conducted using a Morris water maze before and after a subchronic treatment. In cerebral tissue, ACh and acetylcholinesterase (AChE) content and ACh receptor density were determined. Tissue corticosterone concentration was measured in cerebral cortex, hippocampus, and adrenal glands. In corticosterone-treated rats, reduced spatial cognitive abilities were associated with a significant increase in plasma (+25%) and cerebral corticosterone levels (+350%) parallelled by a significant reduction in adrenal gland concentrations (−84%) as compared to placebo. Repeated physostigmine injections improved rats’ spatial memory and increased cerebral ACh and AChE content (p < 0.05). When physostigmine was administered at the same time as corticosterone (group IV), it was not able to reverse the corticosterone effect. A significant correlation was detected between cerebral AChE and corticosterone concentrations as well as between AChE and psychometric parameters. We conclude that subchronic exogenous corticosterone administration induces memory dysfunction whereas physostigmine exerts cognitive-enhancing effects if given for 3 days. An apparently existing interaction between glucocorticoid excess and ACh metabolism is discussed.